Leadership of Madrasah Heads in Developing Tahfidz Curriculum at MI Miftahussudur 01 Dagangan - Izatul A'yun Syaibani; Ali Mudlofir (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2022)
Madrasah are formal educational institutions that have a lot of Islamic studies in them, both from the formal curriculum, as well as supporting superior programs. However, the reality on the ground there are still Madrasah that do not have a superior religious program to support the identity of the madrasah, in fact many of the formal educational institutions that incidentally are not Madrasah that have a superior religious program. Of course this is a problem that must be solved. Therefore, this study aims to find out how the role of the madrasah principal in developing the tahfidz curriculum at Madrasah Ibtidaiyah Miftahussudur 01 Dagangan is to advance the madrasah and as the only superior religious program. This study uses qualitative research with descriptive analysis, while the data collection techniques were obtained through observation, interviews, and documentation. The results of this study indicate that the principal of the madrasah has carried out his duties well in developing the tahfidz curriculum. In addition to having innovation and a good desire for Madrasah, before this program is implemented, madrasah principals also bring in tutors who are experts in the field of the quran to provide training and guidance to teachers for learning methods and also equalize reading quality.Key word: Leadership, curriculum, Tahfidz